If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -7) + (4x) = 110 Reorder the terms: (-7 + 5x) + (4x) = 110 Remove parenthesis around (-7 + 5x) -7 + 5x + (4x) = 110 Combine like terms: 5x + (4x) = 9x -7 + 9x = 110 Solving -7 + 9x = 110 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 9x = 110 + 7 Combine like terms: -7 + 7 = 0 0 + 9x = 110 + 7 9x = 110 + 7 Combine like terms: 110 + 7 = 117 9x = 117 Divide each side by '9'. x = 13 Simplifying x = 13
| j+2=52 | | -12=-5/2x-3 | | 84=y+78 | | 7log(x+92)=14 | | s-9=19 | | c+4=19 | | c/4=3 | | 6-3t=4(2t+7) | | 8=2q | | 85/x=70 | | 5+8v=70 | | 2sin(x/5)cos(x/5) | | 0=-7x^2+2x+9 | | 4x=288 | | -6[7-(-3+2p)]=4(5+3p) | | 3/4*3/7 | | 6(t+8)=90 | | 18x+25y=265 | | -10-8x=-110x+6x | | 1/3*2/7 | | 4n+3m=12 | | .3x+6=7.5 | | 6(K-86)=36 | | 39+x-9*3=25 | | 37=7d-26 | | 4.5(x+2.4)=-13.5 | | 1/7x-8=-3 | | 21+7h=91 | | 9x+3(5x+y)=15 | | 1/3*7/8 | | 88=8(b+2) | | 15x-10=5(2x-7) |